Development of climate-smart maps and adaptation plans for the coastal agriculture in Bangladesh - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Saha, Champa Rani; Rahman, Syed Arman Akib; Haque, Md. Ehsanul; Nisha, Nusrath Jahan; Hosen, Md. Motaleb; Yen, Bui Tan; Nelson, Katherine; Vu, Trang; Vu, Quiet; Tran, Nguyen Bao; et al. (CGIAR Initiative on Asian Mega-Deltas, 2024)
As Bangladesh is predominantly an agricultural country, importance of land and water resources is immense. Land is the basic natural resource from which we derive all ingredients to satisfy our basic needs such as food, raw materials for industrial goods, articles of general use, medicine etc. The gross total area of the country is about 14.8 million hectares (Mha) of which 8.4 million is the net cultivablearea (NCA). Half of the total agricultural land is utilized for double cropping while 13% land is utilized for triple cropping.